Divine Algorithms? Artificial Intelligence and the Reconfiguration of Organized Religion in the Digital Age - EWOH, Edy Ubi (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This article argues that Artificial Intelligence (AI) is not a threat to organised religion, but a transformative partner capable of reshaping religious practice, theology, and organisational structure. Drawing from interdisciplinary and African humanistic scholarship, the study, asks how can AI improve church administration, facilitate evangelisation, help with theological reflection, foster inter-religious dialogue, and how does it pose ethical and doctrinal challenges? The main point is that the ethical use of AI could be a technology and God. That is, the technology and God together enhance religion’s ability to interpret, communicate and humanise in the digital age. The study is conceptual and interpretive in its methodology and is based on critically synthesising literature across theology, media studies, and ethics. Drawing primarily from African perspectives, we present a decolonised framework for the ethics of AI based on communitarian responsibility and spiritual integrity. The analysis shows how AI can be viewed as a medium for the negotiation of moral, cultural, and theological meaning through the contribution to a technological theology. It sees divine agency and digital systems as mutually formed, not at odds with each other. Accordingly, this research contributes to the existing body of knowledge by formulating an ethical-theological framework that positions faith institutions to leverage AI within a construct of pastoral care, inclusive dialogue, and global solidarity, thereby transmuting technological innovation into a moral-spiritual enterprise.